Four‐band electromagnetic energy harvesting with a dual‐layer metamaterial structure. Issue 1 (14th January 2019) - Karakaya, Emrullah; Bagci, Fulya; Can, Sultan; Yilmaz, Asim Egemen; Akaoglu, Baris
Abstract: A four‐band metamaterial harvester for harvesting 0.9 GHz, 1.8 GHz, 2.6 GHz, and 5.8 GHz signals is proposed by a dual‐layer structure. 0.9 GHz and 1.8 GHz bands are harvested by the resistors in front layer, whereas harvesting of 2.6 GHz is achieved by the resistors in second layer. All resistors in front and back layer contribute to harvesting at 5.8 GHz. Numerical calculations are verified by two different full‐wave electromagnetic solvers based on finite‐integration and finite‐element techniques. Power dissipation ratios at 0.9 GHz, 1.8 GHz, 2.6 GHz and 5.8 GHz frequencies concentrated at the resistors are found as 82.3%, 82.8%, 74.6%, and 83.6%, respectively, by the finite‐integration‐based solver. Besides, the finite‐element method‐based solver results in harvesting efficiencies of 79.6%, 93.4%, 73.7%, and 93.8%. The efficiency of the harvester is investigated for different oblique incidences. The proposed metamaterial harvester can be a good candidate for multi‐band absorption and harvesting applications.